COMPUTATION OF WAVE CHARACTERISTICS IN NINH THUAN - BINH THUAN WATERS BY SWAN MODEL ON UNSTRUCTURED GRIDS - Chung, Tran Van; Huan, Nguyen Huu; Hoi, Nguyen Truong Thanh (Vietnam Journal of Marine Science and Technology, 2016)
The wave model SWAN (version 41.01A) with unstructured grid has been applied for Ninh Thuan - Binh Thuan waters. This model is SWAN Cycle III using a vertex-based, fully implicit finite difference method. It can accommodate unstructured meshes with a high variability in geographic resolution suitable for representing complicated bottom topography in shallow areas and irregular shoreline. In particular, the unstructured meshes (triangular meshes) can be used to calculate the flow by finite element method. This is very helpful in solving the problems of interactions between wave-current and wave-wave. The initial results indicate that the approach to SWAN model is reasonable, stable for any time step while permitting local mesh refinements in interested areas. A lot of applications are shown to verify the correctness and numerical accuracy of the unstructured version of SWAN.